Hippocampal AMPA‐ and NMDA‐induced cGMP signals are mainly generated by NO‐GC2 and are under tight control by PDEs 1 and 2. (22nd December 2021) - Giesen, Jan; Mergia, Evanthia; Koesling, Doris; Russwurm, Michael
Abstract: In the central nervous system, the nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) signalling cascade has an established role in fine‐tuning of synaptic transmission. In the present study, we asked which isoform of NO‐sensitive guanylyl cyclase, NO‐GC1 or NO‐GC2, is responsible for generation of N ‐methyl‐d ‐aspartate (NMDA)‐ and AMPA (α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid)‐induced cGMP signals and which of the phosphodiesterases (PDEs) is responsible for degradation. To this end, we performed live cell fluorescence measurements of primary hippocampal neurons isolated from NO‐GC isoform‐deficient mice. Although both isoforms contributed to the NMDA‐ and AMPA‐induced cGMP signals, NO‐GC2 clearly played the predominant role. Whereas under PDE‐inhibiting conditions the cGMP levels elicited by both glutamatergic ligands were comparable, NMDA‐induced cGMP signals were clearly higher than the AMPA‐induced ones in the absence of PDE inhibitors. Thus, AMPA‐induced cGMP signals are more tightly controlled by PDE‐mediated degradation than NMDA‐induced signals. In addition, these findings are compatible with the existence of at least two different pools of cGMP in both of which PDE1 and PDE2—known to be highly expressed in the hippocampus—are mainly responsible for cGMP degradation. The finding that distinct pools of cGMP are equipped with different amounts of PDEs highlights the importance of PDEs for the shape of NO‐induced cGMP signals in the central nervous system. Abstract : In hippocampus, NO/cGMP has an established role in fine‐tuning of synaptic transmission; NMDA and AMPA induce cGMP signals. Using KO mice of the NO‐sensitive cGMP‐generating enzymes (NO‐GC1 and NO‐GC2) and fluorescence‐based live cell imaging, it is demonstrated that NO‐GC1 and predominantly NO‐GC2 mediate NMDA‐ and AMPA‐induced cGMP signals and that these signals, especially the AMPA‐induced ones, are tightly controlled by phosphodiesterases 1 and 2.